Survey Tingkat Kepuasan Mahasiswa PAI Angkatan 2019 Terhadap Pelaksanaan Praktik Pengalaman Lapangan Berbasis Domisili (PPLBD) di UIN Sjech M. Djamil Djambek Bukittinggi - Febi Febrianda; Arifmiboy Arifmiboy; Darul Ilmi; Yelfi Dewi (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
This research was motivated by a new policy issued by UIN Sjech M. Djamil Djambek Bukittinggi at the Faculty of Tarbiyah and Teaching Science (FTIK) as the manager by presenting a Field Experience Practice (PPL) model that was different from the previous year, namely Practice-Based Field Experience. domicile. This was done as an effort to prevent the transmission of the Covid-19 Virus which had just hit Indonesia and of course also had an impact on the implementation of the education system at UIN Sjech M. Djamil Djambek Bukittinggi, so it was necessary to find alternatives related to this problem. This Domicile-Based Field Experience Practice Model involves various parties in its implementation, namely administrators/faculties, supervisors, and tutors who will directly interact with students who will carry out Domicile-Based PPL. This research is a survey research using a quantitative descriptive approach, namely the method used to answer problems using precise measurement techniques for certain variables, resulting in conclusions that can be explained. The data collection techniques for this research were interviews and questionnaires. As the object of research are PAI students class of 2019 who are participating in Domicile-Based PPL. Data analysis was performed by interpreting the recapitulation of the tabulated data obtained. The results of research in the field show that there is a match between the experience gained and felt with the expectations desired by 2019 PAI students who have carried out the process of implementing Domicile-Based PPL. This is based on the recapitulation that has been processed by researchers with the acquisition of a student satisfaction index in the management/faculty domain obtaining a percentage of 72.6% in the satisfied category, for supervising lecturers obtaining a percentage of 76.4% in the satisfied category, and for teachers Pamong gets a percentage of 73.8% in the satisfied category. With the acquisition of these scores, the 2019 batch of PAI student satisfaction index was obtained for the Implementation of Domicile-Based PPL UIN Sjech M. Djamil Djambek Bukittinggi of 74.3% in the satisfied category.